Gastrochilus pechei (Orchidaceae), a new addition to the flora of India - Sahani, Vinay Kumar (2025)
Gastrochilus pechei was recently documented in Vijoynagar, Changlang district, Arunachal Pradesh, India. Identification was based on the spathulate sepals and petals; the acute, sub-triangular, slightly irregularly erose margin of the epichile with a central cushion, and the subglobose hypochile. The species belongs to the section Brachycaules. This report represents a new distribution record for India. An updated description and detailed photographs based on Indian material are provided